Unequal uptake of higher education mobility in the UK. The importance of social segregation in universities and subject areas - Sylke Schnepf (Publications Office of the European Union, 2018)
Student mobility is the most recognised element of Erasmus+, a major EU policy which celebrated its 30th anniversary in 2017. It is clearly popular with an increase in student uptake from 3.2 to 272.5 thousands from 1987 to 2014. Recent studies show that studying abroad provides benefits like improved employment chances and language competences. These benefits are not equally distributed among graduates, since recent literature shows that disadvantaged students are less likely to study abroad than better off students. This is explained by differing social capital of individuals from diverse socio-economic backgrounds which impacts on different choices. However, not much is known about the role of social segregation in universities and subjects studied. Using multilevel logistic regressions this paper examines two main research questions. First, how important is social segregation in universities and subjects for unequal mobility uptake? Second, how much of existing differences in mobility by socio-economic background can be explained by ability of students? Throughout, results for Erasmus mobility will be compared with those of other mobility schemes organised by higher education institutes. The study exploits population data of more than 500,000 UK graduates of the 2010/11, 2012/13 and 2014/15 cohorts deriving from the Higher Education Statistics Agency data (HESA). Results show that a considerable part of unequal mobility uptake is explained by social segregation in universities and subjects even if graduatesâ exteuro™ upper secondary school grades are taken into account. Policy makers aiming to increase mobility uptake of disadvantaged students could allocate resources for mobility more equally across universities.
Keywords: I23; I24; I28; 330; Erasmus; mobility uptake; credit mobility; study abroad; social segregation; UK